Pembuatan Indeks Artikel Surat Kabar Beranotasi Bidang Budaya Sebagai Sarana Penelusuran Informasi di Perpustakaan Umum Gunung Bungsu Kabupaten Tanah Datar Periode 2012 - Khotimah, Husnul; Marlini, Marlini (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2013)
This research explain to describe the process of making an annotated index of newspaper articles of culture as a means of information retrieval in the Library of PUGB Tanah DatarÂ period 2012.Process data collection with interviews and document research by collecting data directly from its original source, the newspaper articles in the Library of PUGB Tanah Datar. The process of making an annotated index of newspaper articles of culture begins with collecting newspapers, selecting and classifying newspapers, making description of the article, make annotations, specify keywords, create indexes newspaper articles, composing and typing articles index. Manufacturing index organized alphabetically newspaper title, author index, and is equipped with a keyword index and annotations. Results of data collection collected 45 titles articles of culture during the period of 2012. Keywords: index; annotations; articles; newspaper